A coupled thermal-hydro-mechanical simulation for carbon dioxide sequestration. Issue 5 (28th August 2014) - Bao, Jie; Xu, Zhijie; Fang, Yilin
Abstract : Herein, the authors present a coupled thermal-hydro-mechanical model, as an improvement of the isotherm hydro-mechanical model in their previous work, for geological sequestration of carbon dioxide followed by stress, deformation, and shear-slip failure analyses. This fully coupled model considers the geomechanical response, fluid flow and thermal transport relevant to geological sequestration. Both analytical solutions and numerical approach by way of finite element model are introduced for solving the thermal-hydro-mechanical model. Analytical solutions for pressure, temperature, deformation and stress field were obtained for a simplified typical geological sequestration scenario by assuming a simplified temperature profile in an aquifer. The finite element model is more general and can be used for arbitrary geometry. It was built on an open-source finite element solver, Elmer, and was designed to simulate the entire period of carbon dioxide injection both stably and accurately – even for large time steps. The shear-slip failure analysis was implemented based on the numerical results from the finite element model. The analysis reveals the potential failure zone caused by the fluid injection and thermal effect. From the simulation results, the thermal effect is shown to reduce the potential failure zone, especially at the early time of the injection.